ARE THE ASSESSMENT CRITERIA AND THE ROLE OF EDUCATIONAL STAKEHOLDERS ABLE TO MAKE OUTSTANDING TEACHER? - Aliyyah, Rusi Rusmiati (International Journal of Psychosocial Rehabilitation, 2020)
The research aims to determine the assessment criteria and the role of education stakeholders in supporting the achievement of elementary school teachers' achievement programs Using a multi- site approach and survey with research respondents consisting of teachers, principals, supervisors, Teacher Working Groups and (KKG) education offices that receive teacher championship performed in 2017 and 2018 in SDN 03 Menteng (DKI Jakarta), SDN Sukasari 5 Tangerang (Banten), SDN Dukuh 3 Salatiga (Central Java), SDN Al-Izhar Pondok Labu (DKI Jakarta), SDN Al-Irsyad Al- Islamiyyah Bekasi (West Java), SDN 12 Dauh Puri (Bali), SDN 023 Pajagalan Bandung (West Java). Data collection was carried out through interviews, questionnaires, documented observation, and discussion group forums. Data analysis techniques using data reduction, data presentation, and verification. The results of the study stated that the primary school teacher's achievement evaluation indicators consisted of portfolios (20%), instructional videos (10%), written tests (20%), scientific papers (20%), presentations of scientific papers (20%), and exemplary (10%). While educational stakeholders play a role by their respective duties and functions.